Studies energy efficiency of the renewable sources use considering climate in Latvia - Sakipova, S.; Jakoviсs, A.; Gendelis, S. (KarU, 2015)
The paper discusses problems of energy supply of buildings using renewable sources given the local climatic conditions. The meteorological conditions in Latvia and Riga for last year were analyzed. In paper shows examples of energy efficient buildings allowing that to provide comfort temperature and indoor air quality. The structure and composition of local building materials, providing good thermal insulation are described. The heating systems for test buildings using renewable energy sources were investigated. The assessment of the energy efficiency of the "air-air" and "air-water" heat pumps is studied.
Keywords: energy efficiency; test buildings; renewable energy sources; energy consumtion; heating system; heat pump